Sompa and Doi Menre in Bugis Bone Marriage and Its Settlement in the Religious Court from the Perspective of Maslahah - Asni, Asni; Tarmizi, Tarmizi; Arisyanti, Arisyanti; Kurniati, Kurniati (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
This study aims to examine the implementation of sompa (dowry or mahr) and doi menre (customary expenditure) and its dynamics in the Bugis Bone community and the problems of its cases in religious courts reviewed from the perspective of Islamic legal maslahah. The study uses empirical legal methods analyzed with the theory of maslahat. Data collection through interviews with several informants in Bone district and document review. The informants interviewed were religious figures, academics and the Bone community, the documents reviewed were the decisions of the Watampone Religious Court related to sompa and doi menre, articles and books and various studies related to the focus of the discussion. The results of the study found that until now the Bugis Bone community still adheres to the dual obligations of sompa (dowry) and doi menre (spending money) in every marriage. However, doi menre as a customary obligation seems to be more prioritized than sompa which is a religious obligation. However, on the other hand, there have also been many shifts that indicate negotiation, investment and transformation so that the implementation of sompa and doi menre seems very dynamic in the social development of Bugis Bone today. Likewise, in the resolution of sompa and doi menre cases in the Religious Court which sometimes accompany divorce cases, it has its own problems that require the creativity of judges in resolving them. From the perspective of maslahah, the dynamics in sompa and doi menre including its resolution in religious courts must be directed towards realizing maslahah and preventing harm so that its existence can remain in line with the positive values ​​that are the goal of Islamic law.